Primeira avaliação genética de populações das espécies Adelophryne maranguapensis Hoogmoed, Borges & Cascon (1994) e Adelophryne baturitensis Hoogmoed, Borges & Cascon (1994) nos brejos de altitude do Ceará - Arruda, Mariny Oliveira (2024)
The world is facing an unprecedented extinction crisis, where current rates of species loss exceed historical standards. With the advent of molecular techniques, conservation genetics emerges as a tool capable of analyzing relevant aspects of species bioecology, especially for threatened species such as amphibians. Therefore, the overall objective of this study was to conduct the first population genetic study of the species Adelophryne maranguapensis and Adelophryne baturitensis, as well as to provide information on the distribution of A. baturitensis in the Serra de Maranguape. For the development of the study, two hypotheses were tested: the first stated that A. baturitensis exhibited higher levels of genetic diversity than A. maranguapensis, as it occurs in four high-altitude bogs in Ceará; the second addressed that A. baturitensis showed different patterns of population structuring and had different population stocks associated with its occurrence areas. Molecular procedures were carried out using DNA sequences generated from 56 tissues deposited at the Regional Nucleus of Ophiology of UFC (NUROF) and 24 sequences available on GenBank. These sequences belonged to individuals collected in the Serra de Maranguape, Serra da Aratanha, Maciço de Baturité, and Planalto da Ibiapaba, and the mitochondrial marker used for the analyses was 16S rRNA. Accordingly, haplotype and nucleotide diversity indices were evaluated, haplotype networks were constructed to examine gene flow, and Analysis of Molecular Variance (AMOVA) was performed to observe genetic variability within and between populations. Based on the results, we concluded that the hypotheses were refuted, as we observed that, despite the species A. maranguapensis being critically endangered, it exhibited higher diversity indices compared to A. baturitensis. The absence of population structure in A. baturitensis was evidenced, and the four populations known for the species appear to consist of a single population stock. Furthermore, the results regarding genetic variability in populations showed that Adelophryne maranguapensis and Adelophryne baturitensis are species that do not share gene flow. In addition to this assessment, our study contributed new information on the occurrence and identification of A. baturitensis in the Serra de Maranguape. We found that this species occurs in syntopy with A. maranguapensis, occurring at altitudes above 600 meters and utilizing bromeliad microhabitats